Hubungan Pengetahuan Gizi, Pola Makan, dan Aktivitas Fisik dengan Kejadian Status Gizi Lebih pada Remaja di Man 2 Jakarta Timur: The Relationship of Nutrition Knowledge, Eating Pattern, and Physical Activity with The Incidence of Overnutrition Status in Adolescents at MAN 2 East of Jakarta - Fadhelina Luthfiah Azzahra; Inne Indraaryani Suryaalamsah (JURNAL GIZI DAN KESEHATAN, 2024)
The problem of excess nutritional status in adolescents has an 80% chance of being obese as an adult. In 2018, Basic Health Research Data (Riskesdas) reported that Indonesia had a prevalence of obese nutritional status of 11.3% in adolescents aged 13 - 15 years. Overnutrition that occurs in adolescents can continue into adulthood and can cause non-communicable diseases such as cardiovascular disease, diabetes and cancer. This study aims to determine the relationship between nutritional knowledge, diet, and physical activity with overweight status in adolescents at MAN 2, East Jakarta. This research is a quantitative observational study with a cross-sectional design. The number of samples is 54 respondents taken by simple random sampling technique. The research instrument used a nutritional knowledge questionnaire, a semi-quantitative food frequency questionnaire (SQ-FFQ), a physical activity level (PAL) questionnaire, and anthropometric data. Research result show that as many as 36% of adolescents had malnutrition status, 34% of adolescents had good nutritional knowledge, 32% of adolescents had poor eating patterns, and 34% of adolescents with mild physical activity. For the results of bivariate analysis using the chi square test, it was found that all variables in this study had a significant relationship (p ≤0.05) with the incidence of overweight in adolescents at MAN 2, East Jakarta.   ABSTRAK Masalah status gizi lebih pada remaja memiliki peluang 80% dengan kejadian obesitas saat dewasa. Data Riset Kesehatan Dasar (Riskesdas) Tahun 2018 melaporkan bahwa Indonesia memiliki prevalensi status gizi gemuk sebanyak 11,3% pada remaja usia 13 – 15 tahun. Gizi lebih yang terjadi pada remaja dapat berlanjut hingga usia dewasa dan dapat menimbulkan penyakit tidak menular seperti kardiovaskular, diabetes, dan kanker. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan gizi, pola makan, dan aktivitas fisik dengan status gizi lebih pada remaja di MAN 2 Jakarta Timur. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan gizi, pola makan, dan aktivitas fisik dengan status gizi lebih pada remaja di MAN 2 Jakarta Timur. Hasil penelitian menunjukkan bahwa anyak 36% remaja memiliki status tidak gizi lebih, 34% remaja memiliki pengetahuan gizi baik, 32% remaja memiliki pola makan tidak baik, dan 34% remaja dengan aktivitas fisik ringan. Untuk hasil analisis bivariat menggunakan uji chi square didapatkan hasil yaitu seluruh variabel pada penelitian ini memiliki hubungan yang signifikan (p ≤0,05) dengan kejadian status gizi lebih pada remaja di MAN 2 Jakarta Timur.